Anatomical Study of Red-eared TurteTail (Trachemys scripta elegans) - Nofita, Putri; Luthfi, Muhammad Ja’far; Dewi, Reza Sukma (Proceeding International Conference on Science and Engineering, 2019)
Turtles are reptiles armored backs hard, slow motion, appearing for the first time about 200 million years ago and relative ly unchanged for 150 million years. This study aims to determine the anatomical structure of the axial skeleton and determine the histologic structure of red-eared turtles (Trachemys scripta elegans) females. The method used, among others, Alizarin Red S staining Alcian Blue, methods of paraffin with Hematoxylin-eosin staining (HE) and Mallory acid fuchsin and used 3 adult turtles 3 years old. The results showed that vertebral caudalis red-eared turtles (Trachemys scripta elegans) females composed of true bone, vertebrae-type amphicoelous not have plains autotomy and histology red-eared turtles (Trachemys scripta elegans) females resemble histological structure other tail reptiles with some differences that only have 4 files do not have the muscle and fat tissue.